8th Agronomists’ National Workshop Report Ashad 30-31, 2070 (14-15 July 2013) - Nepal, Agronomy Society of (Agronomy Journal of Nepal, 2013)
Jointly Organized by Crop Development Directorate and Agronomy Society of Nepal Agronomy Journal of Nepal (Agron JN) Vol. 3. 2013, Page 181-191 DOI: http://dx.doi.org/10.3126/ajn.v3i0.9021